Random trees an interplay between combinatorics and probability - Drmota, Michael. (Springer, 2009)
Classes of Random Trees -- Generating Functions -- Advanced Tree Counting -- The Shape of Galton-Watson Trees and Pólya Trees -- The Vertical Profile of Trees -- Recursive Trees and Binary Search Trees -- Tries and Digital Search Trees -- Recursive Algorithms and the Contraction Method -- Planar Graphs.